2020
DOI: 10.1111/tbj.13921
|View full text |Cite
|
Sign up to set email alerts
|

Drain secretion and seroma formation after immediate breast reconstruction with a biological and a synthetic mesh, respectively: A randomized controlled study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Of 603 searched studies through the PubMed, MEDLINE, and Embase databases, following their review by two independent reviewers, 61 studies were included for the full-text reading, of which 17 studies were finally included for the network meta-analysis [2,3,5,9,[12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Of 603 searched studies through the PubMed, MEDLINE, and Embase databases, following their review by two independent reviewers, 61 studies were included for the full-text reading, of which 17 studies were finally included for the network meta-analysis [2,3,5,9,[12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Alloderm-RTU and DermACELL are considered to be amongst the more popular but also more expensive ADM products in the breast reconstruction market. Alternative synthetic meshes such as those used for hernia repairs are also being used in breast reconstruction and are relatively less expensive [ 22 , 43 ]. The purpose of the study was to evaluate the two most commonly used ADM’s.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of the study was drain duration. The literature reports the mean drain duration for subpectoral immediate prosthetic based reconstruction with ADM to be in the range of 8–12 days [ 19 , 21 , 22 , 23 ]. As such, the plastic and breast surgeons in this study determined that a minimum of 4 days in drain duration between the two arms was considered clinically significant.…”
Section: Methodsmentioning
confidence: 99%
“…The study is reported according to the CONSORT guidelines 17 . Previously, complications 6 , drain secretion 18 , and histological findings 19 have been reported for the participants. The study was vetted and approved by the Regional Ethical Committee of Gothenburg (189-16) and conducted in accordance with the Helsinki Declaration and the Good Clinical Practice (GCP) guidelines.…”
Section: Study Design Protocol and Ethicsmentioning
confidence: 98%